2021
DOI: 10.1038/s41598-021-94065-z
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas-9 mediated knock-in by homology dependent repair in the West Nile Virus vector Culex quinquefasciatus Say

Abstract: Culex quinquefasciatus Say is a mosquito distributed in both tropical and subtropical regions of the world. It is a night-active, opportunistic blood-feeder and vectors many animal and human diseases, including West Nile Virus and avian malaria. Current vector control methods (e.g. physical/chemical) are increasingly ineffective; use of insecticides also imposes hazards to both human and ecosystem health. Advances in genome editing have allowed the development of genetic insect control methods, which are speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The impact of longer repair template insertion on knock-in efficiency is yet to be determined. Efficient insertion of larger fragments in insects have been reported using donor dsDNA template, including the use of long donor dsDNA plasmids for HDR ( Gilles et al., 2015 ; Ma et al., 2014 ; Purusothaman et al., 2021 ), microhomology-mediated end joining in Bombyx ( Nakade et al., 2014 ), and the homology-independent end-joining of plasmid cassettes ( Bosch et al., 2020 ; Matsuoka et al., 2021 ). These approaches are promising avenues for optimizing larger cassette insertion in Plodia genome, the third lepidopteran organism after Bombyx, and Plutella where germline-heritable CRISPR HDR edits are reported ( Takasu et al., 2016 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of longer repair template insertion on knock-in efficiency is yet to be determined. Efficient insertion of larger fragments in insects have been reported using donor dsDNA template, including the use of long donor dsDNA plasmids for HDR ( Gilles et al., 2015 ; Ma et al., 2014 ; Purusothaman et al., 2021 ), microhomology-mediated end joining in Bombyx ( Nakade et al., 2014 ), and the homology-independent end-joining of plasmid cassettes ( Bosch et al., 2020 ; Matsuoka et al., 2021 ). These approaches are promising avenues for optimizing larger cassette insertion in Plodia genome, the third lepidopteran organism after Bombyx, and Plutella where germline-heritable CRISPR HDR edits are reported ( Takasu et al., 2016 ; Wang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…aegypti 10,35 and Cu. quinquefasciatus, 38 but significantly lower than the gene knockout frequency mediated by the NHEJ repair pathway, 10,[34][35][36]40 and lower than the transposon mediated transgenic frequency of An. sinensis.…”
Section: Discussionmentioning
confidence: 85%
“…Since its discovery, the CRISPR/ Cas9 system has revolutionized genome editing and has been successfully applied to a diverse range of insect species, including members of the Diptera, Lepidoptera, Hymenoptera, Hemiptera, Orthoptera, and Coleoptera. 18,[22][23][24][25][26][27][28][29][30][31][32][33] The CRISPR/Cas9 system has been applied in studies on mosquito species such as Aedes aegypt, 10,34,35 Aedes albopictus, 36 Culex quinquefasciatus, 37,38 Anopheles gambiae, 39 Anopheles albimanus, 40 Anopheles coluzzii, 40 Anopheles funestus, 40 and Anopheles stephensi. 41 These studies showed that CRISPR/Cas9 is a strong tool that could be used to uncover the mechanistic knowledge of myriad mosquito biological processing.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti fitness effects were not measured (18, 39). In our own recent experience with Culex quinquefasciatus kmo -/- could be generated and maintained as homozygotes, but an insertional mutant expressing a fluorescent protein was homozygous lethal (43, 44). Using these best fit parameter values within the stochastic model shows that experimental results fall within the expected range.…”
Section: Resultsmentioning
confidence: 99%